Efficacy and Rice Phytotoxicity of Different Tank-Mix Ratios of Pre-Emergence Herbicide in Boro Rice Under Zero Till Non-Puddled Condition - Amodini Hossain; A K M Mominul Islam; Md. Wakilur Rahman; Md. Parvez Anwar (Fundamental and Applied Agriculture, 2025)
Tank-mixing two or more chemical groups of either pre- or post-emergence herbicide may be very beneficial for the efficient control of weeds in a heterogeneous population. There are a few proprietary herbicides (commercial mixtures of two pre- or post-emergence herbicides) on the market, but they are extremely few. In this backdrop, the current research was conducted to investigate the efficacy and rice phytotoxicity of different tank-mix ratios of pre-emergence herbicides to control weeds under zero till non-puddled Boro rice (cv. BRRI dhan58). A total of 21 treatments were used in the experiment. Treatments comprised five pre-emergence herbicides with their 20 different tank-mix ratios and one proprietary pre-emergence herbicide as control. The experiments were conducted under randomized complete block design with three replications. The findings of this research indicate that different tank-mix ratios of pre-emergence herbicide have a great potential to control weeds and the applied herbicide mixtures have not create any phytotoxicity to the rice plants. The lowest weed dry biomass was obtained from the treatment where Triafamone and Pretilachlor @ 2:3 ratios were applied in both 30 and 60 DATs, and highest weed dry biomass was from treatment Triafamone and Pretilachlor @ 3:2 ratios. Considering the yield contributing characters and yield, the highest number of effective tillers hill-1, longest panicle, heaviest grain and highest grain yield of BRRI dhan58 were also obtained from the treatment where Triafamone and Pretilachlor @ 2:3 ratios were applied. Based on the results it may conclude that tank-mix pre-emergence herbicide Triafamone and Pretilachlor @ 2:3 ratios is the best in terms of weed control and rice productivity. However, as this experiment had been conducted in a single season and location, multi-location and multi-season trials should be taken into account in future to draw a concrete conclusion based on these preliminary experimental results. [Fundam Appl Agric 2025; 10(1.000): 326-332]